IoT-based Home Water Monitoring using Arduino - Rosyady, Phisca Aditya; Yulianto, Dinan; Warsino , Fathiyyah (Universitas Ahmad Dahlan, 2021)
There are many problems related to water in Indonesia, ranging from floods to water crises. One of the things we can do is manage water consumption so that we can use water effectively and wisely. The problem of excessive anggd unwise water use can be overcome by water consumption management.. In this study, a water consumption management system incc the household is created, which includes monitoring and control so that we can monitor and control it and also have a history of daily water use. The system will be made using Arduino Uno as controller and will be displayed on the LCD and the website. Based on research, the following conclusions were obtained: Successfully implemented IoT based home water monitoring using Arduino, Successfully designed a tool for water tank management based on Arduino Uno, the results obtained by the tool can detect when the water is full, and the water pump turns off automatically so that the water does not fill again and the tank will not be full. The average error of this system is 6.16 %. The bigger volume will make the error value decrease.